The Influence of Effort Expectancy and Digital Facilitating Conditions on Use Behavior of Online Expedition Service - Sonya Sidjabat; Edi Abdurachman; Edhie Budi Setiawan; Hartiwi Prabowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Indonesia’s rapidly expanding digital economy has made online expedition services a crucial component of e-commerce last-mile delivery. However, the determinants of actual usage behavior, particularly the role of demographic factors, remain insufficiently explored. This study examines the direct effects of effort expectancy, social media influence, and digital facilitating conditions on use behavior, as well as the mediating role of age among Indonesian users of online expedition services. Using a quantitative approach, data were collected from 250 purposive respondents who had used major expedition platforms within the past six months and analyzed using partial least squares structural equation modeling. The results indicate that all three antecedents have significant positive effects on use behavior, with effort expectancy emerging as the strongest predictor. Age shows a significant direct effect and mediates the relationships between the three predictors and use behavior. The model explains 68% of the variance and demonstrates strong predictive relevance. These findings underscore the importance of usability, social influence, and digital support, while highlighting age as a key factor shaping adoption. Online expedition providers should therefore focus on user-friendly platforms, active social media strategies, and inclusive digital infrastructure to increase adoption across age groups.